2020
DOI: 10.1021/acs.orglett.0c01892
|View full text |Cite
|
Sign up to set email alerts
|

[n]Dendralenes as a Platform for Selective Catalysis: Ligand-Controlled Cu-Catalyzed Chemo-, Regio-, and Enantioselective Borylations

Abstract: We report the development of two complementary methods for the Cu-catalyzed anti-Markovnikov borylation of one specific olefin in 2-substituted [n]­dendralenes (n = 3–6). The first protocol operates with a bisphosphine ligand and occurs with high regio- and chemoselectivity for the terminal double bond, independently of the number of cross-conjugated alkenes. We show that the use of a chiral phosphanamine ligand enables the highly chemo-, regio-, and enantioselective borylation of the alkene cross-conjugated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The same research group adopted an identical methodology to synthesize [n]dendralenes by the Kumada reaction of vinyl phosphate 7 – 2 ( Scheme 7 ) [ 56 ]. In this process, readily available phosphate 7 – 2 was subjected to a reaction with related Grignard reagents under different conditions.…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…The same research group adopted an identical methodology to synthesize [n]dendralenes by the Kumada reaction of vinyl phosphate 7 – 2 ( Scheme 7 ) [ 56 ]. In this process, readily available phosphate 7 – 2 was subjected to a reaction with related Grignard reagents under different conditions.…”
Section: Organophosphates As Electrophiles In Transition-metal-cataly...mentioning
confidence: 99%
“…53 After the work of Sherburn et al on [n]dendralenes, Mazet et al reported a modular synthetic route to access 2substituted [n]dendralenes using a Ni-catalyzed Kumada cross-coupling protocol for the synthesis of 2-substituted 1,3-dienes (Scheme 41). 52,54 The starting dienol phosphate was prepared in high yield by treatment of 3-phenylbut-3-en-2-one with LDA at −78 °C, followed by addition of diethyl chlorophosphite (1.5 equiv). With the [NiCl 2 (dmpe)] as catalyst, dienyl phosphates were cross-coupled with different vinylmagnesium bromide reagents leading to the desired [n]dendralenes from low to satisfactory yields.…”
Section: Enol Mesylatementioning
confidence: 99%
“…The Cu-catalyzed borofunctionalization of π systems has emerged as an enabling approach for installing a C–B bond and simultaneously a vicinal C–H, C–C, or C–heteroatom bond across readily accessible unsaturated systems . Because of the central role of organoboron compounds, the growing interest observed for this strategy stems from the rapid access it offers to polyfunctional frameworks containing contiguous sp 2 - or sp 3 -hybridized carbon atoms using a nontoxic earth-abundant metal. , The commonly admitted mechanism for these reactions involves migratory insertion of a Cu–boryl species across the π system followed by trapping of the alkyl–copper intermediate by an electrophile and subsequent demetalation. , To date, diversely substituted cyclic and linear alkenes, 1,3-dienes, allenes, alkynes, enynes, and even dendralenes have been engaged in Cu-catalyzed borofunctionalization reactions. ,, These have been combined with more than 20 different electrophiles, including alkyl halides, aryl halides, aldehydes, ketones, imines, carbon dioxide, amines, or isocyanates, to name just a few (Figure A).…”
mentioning
confidence: 99%
“… 3 , 4 To date, diversely substituted cyclic and linear alkenes, 1,3-dienes, allenes, alkynes, enynes, and even dendralenes have been engaged in Cu-catalyzed borofunctionalization reactions. 1 , 3 , 5 These have been combined with more than 20 different electrophiles, including alkyl halides, aryl halides, aldehydes, ketones, imines, carbon dioxide, amines, or isocyanates, to name just a few ( Figure 1 A).…”
mentioning
confidence: 99%